Intelligent wearable interfaces - Xu, Yangsheng, 1958- (Wiley-Interscience, 2008)
This book introduces methodologies to develop a variety of?wearable interfaces??small body-worn intelligent machines that are always with the user and are designed to be useful in mobile settings. The authors address the development of these intelligent.